The Development of Covid-19 Dashboard Application for Monitoring the Covid-19 Infections in Indonesia - abraham mahanaim; salma aziizah novrian; normalisa (Liaison Journal of Engineering, 2023)
In this Era where global pandemic is rampant, there is a need for accurate and up-to- date information for people to know, understand and monitor the movement of the virus. This abstract will explain about COVID-19 Dashboard app design to visualize the COVID-19 infection data, this dashboard can be used to monitor and also analyze pandemic impact in Indonesia. This app uses COVID-19 csv data sourced from trusted Indonesian Organization to present reliable data so the app can present statistical data such as the number of confirmed cases, deaths, recoveries, and other insight related to pandemics. By using interactive sidebars users can explore the data or change the type of graphs. This app aims to be able to help individuals, travelers, healthcare professionals, and others to gain insight regarding pandemic situations in Indonesia and also hopefully increase the situational awareness of each individual. Keywords: Covid-19; Monitor Dashboard; Paper; University Liaison Indonesia